The Legal Culture of ‘Trust’ in the Swedish State by Religious Communities seen through the lens of the Pandemic (Stato, Chiese e pluralismo confessionale, 2022)
TABLE OF CONTENTS: 1. Introduction - 2. The Protection of Religious Freedom within the Swedish Constitutional Framework - 3. Sweden as a sui generis Legal Order within Europe during the Pandemic and the Specificity of the Measures adopted to counter Covid-19 - 4. Religious Freedom in Sweden during the Covid-19 Pandemic. A Subordinated Protection based on a Trust-Oriented Response - 5. The Legal Culture of ‘Trust’ in the State as the Grounds for the ‘Respectful Collaboration’ of Religious Communities.ABSTRACT: The Covid pandemic has an enormous impact on individual rights. This is true also for the freedom to manifest one’s religion and Sweden represents an exceptional case study because the strategies the Swedish Government has adopted to limit the spread of the virus are distinct from those adopted in other European countries. The article will first analyse Swedish constitutional provisions with reference to the protection of religious freedom. Second, the article will offer some examples concerning the distinguishing features of the measures adopted by the Swedish Government. Third, attention will be dedicated to the analysis of the conduct of the Church of Sweden and of other religious communities with regard to the governmental decisions to counter Covid-19. The main argument of this article is that the concept of ‘Trust’ can both justify the responses of the religious communities and be used in the broader perspective of the upcoming legislative reforms regarding religious communities.